2005
DOI: 10.3748/wjg.v11.i46.7261
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of rapid urine trypsinogen-2 test strip, urinary trypsinogen activation peptide, and serum and urinary activation peptide of carboxypeptidase B in acute pancreatitis

Abstract: In patients with acute abdominal pain, hospitalized within 24 h of symptom onset, CAPAP in serum and urine was a reliable diagnostic marker of acute pancreatitis. Urinary trypsinogen-2 test strip showed a clinical value similar to amylase and lipase. Urinary TAP was not a useful screening test for the diagnosis of acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
0
24
1
4
Order By: Relevance
“…Plasma and urine levels of TAP have been found to be elevated and predictive of the development of acute pancreatitis [85,86] . However, this finding was not validated in other reports [87,88] . In a study looking specifically at post-ERCP patients, urinary TAP was not found to be useful in predicting mild PEP.…”
Section: Category 2: Markers Of Proteolytic Activationcontrasting
confidence: 53%
“…Plasma and urine levels of TAP have been found to be elevated and predictive of the development of acute pancreatitis [85,86] . However, this finding was not validated in other reports [87,88] . In a study looking specifically at post-ERCP patients, urinary TAP was not found to be useful in predicting mild PEP.…”
Section: Category 2: Markers Of Proteolytic Activationcontrasting
confidence: 53%
“…Gallstones were the most common causes of AP (n = 58, 63%), while familial Mediterranean fever and acute appendicitis were the most common causes of acute abdominal pain in patients in the control group (n = 5, 20% and n = 5, 20%, respectively) ( Table 1). Mean BMI of patients in the study and control groups were 24.0 ± 3.8 kg/m 2 (range, 16-33) and 23.5 ± 3.4 kg/m 2 (range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], respectively (P = 0.902). Both mean serum amylase concentrations and mean serum lipase concentrations were significantly higher in patients in the study group compared with those in the control [amylase, 600.8 ± 189.7 U/L (range, 376-1250) vs 67 ± 32.5 U/L (range, 18-176), and lipase, 96.2 ± 42.4 U/L (range, 58-230) vs 33.8 ± 15 U/L (range, 13-65); P = 0.000)].…”
Section: Resultsmentioning
confidence: 99%
“…Kemppainen et al 1997 [29] 94 95 Kylanpaa-Back et al 2000 [28] 96 92 Lempinen et al 2001 [5] 62 87 Pezzilli et al 2001 [27] 53.3 -Lempinen et al 2003 [7] 72 81 Chen et al 2005 [16] 89.6 85.7 Saes et al 2005 [30] 68 86. mild abdominal discomfort to multiple organ failure. After a mild pancreatitis attack, 80% of patients recover completely, while the disease worsens in 20% and has a mortality rate of 30% [1,[17][18][19] .…”
Section: Ap Presents In Various Clinical For Ms Ranging Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have advocated the use of urinary trypsinogen-2 as a screening tool, with a positive result indicating a need for further evaluation of acute pancreatitis. [18][19][20] Urinary trypsinogen-2 is less costly than serum tests, plus may result in additional cost savings with earlier patient discharge. Unfortunately, this test is not widely available for clinical use.…”
Section: Etiologymentioning
confidence: 99%